Integrated nutrient management, soil fertility, and sustainable agriculture: current issues and future challenges - Gruhn, Peter; Goletti, Francesco; Yudelman, Montague (International Food Policy Research Institute, 2000)
The challenge for agriculture over the coming decades will be to meet the world’s increasing demand for food in a sustainable way. Declining soil fertility and mismanagement of plant nutrients have made this task more difficult. In this brief, Peter Gruhn, Francesco Goletti, and Montague Yudelman point out that as long as agriculture remains a soil-based industry, major increases in productivity are unlikely to be attained without ensuring that plants have an adequate and balanced supply of nutrients. They call for an Integrated Nutrient Management approach to the management of plant nutrients for maintaining and enhancing soil, where both natural and man-made sources of plant nutrients are used. The key components of this approach are described; the roles and responsibilities of various actors, including farmers and institutions, are delineated; and recommendations for improving the management of plant nutrients and soil fertility are presented.